2007
DOI: 10.1897/06-621
|View full text |Cite
|
Sign up to set email alerts
|

Estimating dioxin-like polychlorinated biphenyl toxic equivalents from total polychlorinated biphenyl measurements in fish

Abstract: Polychlorinated biphenyls (PCBs) are 209 related compounds, a dozen of which are known as dioxin‐like PCBs (dl‐PCBs) and are among the most toxic PCBs. Polychlorinated biphenyls contribute to many adverse effects to human health, including cancer, and are a major cause of fish advisories in North America. It is a common perception that individual PCB compounds, especially dl‐PCBs, rather than total PCB need to be quantified to predict the environmental hazard because of differences in their toxicity potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 25 publications
6
20
0
Order By: Relevance
“…It is shown that the composition of Aroclor Dl-PCBs and marker PCBs concentrations appeared to be linearly correlated (R 2 =0.90; Fig. 3) as it has been previously reported by other authors for bottom sediments from Rhone River (Okay et al 2009) and proved to be also a common feature in fish (Bhavsar et al 2007;Stachel et al 2007). …”
Section: Levels and Sources Of Pcdd/fs And Pcbs In Sedimentssupporting
confidence: 81%
“…It is shown that the composition of Aroclor Dl-PCBs and marker PCBs concentrations appeared to be linearly correlated (R 2 =0.90; Fig. 3) as it has been previously reported by other authors for bottom sediments from Rhone River (Okay et al 2009) and proved to be also a common feature in fish (Bhavsar et al 2007;Stachel et al 2007). …”
Section: Levels and Sources Of Pcdd/fs And Pcbs In Sedimentssupporting
confidence: 81%
“…Many studies have reported PCB 118 as the major congener of PCBs in fish (Bhavsar et al, 2007). In the present study, this congener was also identified as the major contributor to the PCB concentrations in the fish samples.…”
Section: Discussionsupporting
confidence: 69%
“…Some limitations of earlier data were overcome by using recent data on congener ratios to estimate the concentrations of congeners not previously measured (e.g., Bhavsar et al, 2007bBhavsar et al, , 2008.…”
Section: Variables Affecting Temporal Trendsmentioning
confidence: 99%
“…However, TEQs for PCDD/Fs in LO eels in 1980 (Ryan et al, 1984) and 1993(MOE, 2012 were estimated from mean concentrations of PCDD/Fs and the mean ratio of TEQs:PCDD/Fs calculated from data of the present study (Tables 2 and 4). Similarly, TEQs for PCBs (mo + no congeners) were calculated from measurements in 1980 (Ryan et al, 1984) and 1993(MOE, 2012 using the mean ratio of TEQs:PCBs of eels from the present study (Tables 2 and 4), a method validated for other Great Lakes fish (Bhavsar et al, 2007b). Estimated mean TEQ concentrations were 59.5 ± 35.6 and 14.4 ± 6.9 pg/g ww for eels collected in 1980 and 1993, respectively.…”
Section: Potential Effects Of Toxic Chemicals On Eel Recruitmentmentioning
confidence: 99%